2013
DOI: 10.1186/2193-1801-2-347
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic and toxigenic ability of opportunistic fungi contaminating intensive care units and operation rooms at Assiut University Hospitals, Egypt

Abstract: Total of 110 isolates belonging to 8 fungal species collected from intensive care units (ICUs) and operation rooms (ORs) at Assiut University hospitals were examined for their ability to produce some extracellular enzymes and mycotoxins which are considered as important factors involved in for fungal pathogenicity. The results revealed that 73, 92 and 78 out of the 110 tested isolates produced protease, lipase and urease respectively; meanwhile, 77 of the tested isolates exhibited some hemolytic activities. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
2
12
0
1
Order By: Relevance
“…There have been previous reports on leaf blight disease of water hyacinth that are caused by the genera of Myrothecium , which are widely distributed in different continents, including Thailand (Evans & Reeder ). Similarly to the current study, the isolates of M. roridum have been reported to have specificity to water hyacinth and to produce enzymes and mycotoxins (Aboul‐Nasr et al ). A recent report showed that M. roridum produced cell wall‐degrading enzymes (Okunowo et al ) and macrocyclic trichothecene mycotoxins, such as Verrucarin A & J and Roridin A & E (Jarvis et al ; Abbas et al ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…There have been previous reports on leaf blight disease of water hyacinth that are caused by the genera of Myrothecium , which are widely distributed in different continents, including Thailand (Evans & Reeder ). Similarly to the current study, the isolates of M. roridum have been reported to have specificity to water hyacinth and to produce enzymes and mycotoxins (Aboul‐Nasr et al ). A recent report showed that M. roridum produced cell wall‐degrading enzymes (Okunowo et al ) and macrocyclic trichothecene mycotoxins, such as Verrucarin A & J and Roridin A & E (Jarvis et al ; Abbas et al ).…”
Section: Discussionsupporting
confidence: 64%
“…Myrothecium roridum infects water hyacinth due to the activity of its enzymes and mycotoxins (Okunowo et al ). Okunowo et al () reported that M. roridum produces cellulases and xylanases, while Aboul‐Nasr et al () determined that M. roridum has the ability to produce mycotoxic compounds, such as Roridin A & E and Verrucarin A & J.…”
mentioning
confidence: 99%
“…The hemolysin produced by A. fumigatus (asp-hemolysin) promotes Aspergillosis, and may also promote opportunistic infections [58]. Aboul-Nasr et al isolated 77 fungal isolates from Assiut University Hospitals exhibited some hemolytic activities and mentioned that those isolates represent a risk factors on patients in Assiut university hospitals [59].…”
Section: Resultsmentioning
confidence: 99%
“…To enable a more accurate identification and prediction of hospitalacquired fungal outbreaks, including exposure to their extracellular enzymes and mycotoxins, a total of 110 isolates belonging to 8 fungal species collected from intensive care units (ICUs) and operating rooms (ORs) at Assiut University Hospital in Egypt were examined for their ability to produce extracellular enzymes and mycotoxins that are considered important in fungal pathogenicity [6]. El-Kady and Moubasher [57] showed that 73, 92 and 78 of the 110 tested isolates produced protease, lipase and urease, respectively.…”
Section: Extracellular Enzyme Pathogenicitymentioning
confidence: 99%
“…The total annual asthma cost attributable to exposure to dampness and mold, calculated by multiplying the selected estimate of costs by the attributable fraction of 21%, is approximately $3.5 billion [4]. Moreover, reported cases of hospital-acquired fungal infections in hospitalized and immunosuppressive patients are on the rise [5][6][7][8]. Other groups at risk, such as the elderly [9] and young children [10,11], have been noted for their susceptibility to the harmful effects of indoor air and fungi.…”
Section: Introductionmentioning
confidence: 99%